ANALISIS PERTUMBUHAN EKONOMI PER KABUPATEN/KOTA DI PROVINSI DIY - ARINI NURLITASARI; RIFKI KHOIRUDIN (LP2MTBM MAKARIOZ, 2021)
This study aims to determine and analyze whether the district minimum wage, human development index, labor forceparticipation rate, and dependency ratio have an influence on economic growth in districts/cities in the Special Region ofYogyakarta Province. This research is quantitative descriptive. This study uses panel data, panel data is a combination ofdata from time series and cross section data. The data collection method used is a library research method obtained fromthe BPS (Badan Pusat Statistik) website for the period 2010-2019. The results showed that: 1) the minimum wage variablehas an influence on economic growth, 2) the labor force participation rate variable has an influence on economic growth, 3)the human development index variable has no effect on economic growth, 4) and the dependency ratio variable does not.have an influence on economic growth. From the regression results, the adjusted r-squared value is 0.847842 which meansthe district minimum wage, human development index, labor force participation rate and dependency ratio are able to explaineconomic growth of 84.78% and the remaining 15.22% is explained by other variables outside the model.